Digitalization of Government Management Processes in the Context of Sustainable Development - Sira Mariya; Kuzior Aleksandra (Management Systems in Production Engineering)
This study examines how integrating digital technologies into government operations can enhance urban governance in smart cities. It specifically looks at how these advancements can contribute to the development of sustainable smart cities in alignment with the Sustainable Development Goals (SDGs). The research employs two analytical frameworks to assess how advanced technologies impact and integrate with government functions. The first framework examines the effects of digitalization on sustainable smart cities, while the second offers a holistic approach to optimizing government processes through digital transformation. The research demonstrates the various advantages of digitalization, such as enhanced public services, advanced infrastructure, and greater transparency and accountability. Nevertheless, obstacles like data security, privacy issues, and disparities in digital access are recognized, requiring cautious handling. The research affirms that while integrating digital technologies in government operations can significantly support urban sustainability, the strategy is crucial to manage potential threats and foster inclusivity and environmental responsibility. These models provide practical recommendations for governments to responsibly and effectively utilize digital tools, ultimately fostering the development of resilient, efficient, and inclusive smart cities.